Telomerase activity pattern in somatic tissues of the bumblebee (B. terrestris) - Freytag, Matilda Emily (Jihočeská univerzita, 2020)
In this thesis it was determined if the telomerase activity pattern of primitive eusocial insects, like Bombus terrestris (bumblebee), differs from the one already previously found in advanced eusocial insects, like for example Apis mellifera (honeybee). The telomerase activity of the somatic fat body tissue and the telomerase activity of larvae of B.terrestris were tested using TRAP assay. Possible influences of the life cycle of primitive eusocial insects, the mating process of queens and the endocrine regulation on the observed telomerase activity patterns are discussed.
Telomerase activity pattern in somatic tissues of the bumblebee (B. terrestris)
Keywords: eusocial insect; bumblebee; honeybee; telomerase; telomere length; larvae; endocrine regulation; diapause; cell proliferation; eusocial insect; bumblebee; honeybee; telomerase; telomere length; larvae; endocrine regulation; diapause; cell proliferation